Longitudinal Patterns in the Isolation and Antimicrobial Resistance of Bovine Mastitis-Causing Bacteria in Ireland - Amalia Naranjo-Lucena; Philip Becker; Gillian Madigan; Rebecca Cupial; Brian Byrne; Alan Johnson (Antibiotics)
Background/Objectives: Bovine mastitis remains a challenge for the Irish dairy industry. This study aimed to explore the seasonality and antimicrobial resistance of mastitis pathogens obtained by the regional laboratories (RVL) of the Department of Agriculture, Food and the Marine. Methods: Seasonality of isolation of the most common bacterial species and antimicrobial resistance of those species repeatedly obtained in the same herds in different years were explored using the RVL diagnostic data. Additionally, whole genome sequencing (WGS) was employed to establish the persistency of Staphylococcus aureus strains within the same herd. Results: A clear seasonality was observed in the isolation of Staphylococcus aureus, Streptococcus uberis, and Escherichia coli from milk. Seasonal differences were statistically significant within and between bacterium. Persistence of resistance within herds was highest in S. aureus against penicillin (35.5% of herds) and in S. uberis against pirlimycin (14% of herds), while E. coli did not show persistence of resistance to any antimicrobials. Sequencing of S. aureus isolates revealed that the strains causing mastitis in ten out of twenty-one herds were similar genetically in different years. In seven of these herds, S. aureus was persistently resistant to penicillin. Isolates from two different herds were practically identical and carried the human immune evasion cluster genes (IEC, scn, sak, chp and sea) suggesting a recent human-bovine host switch event. Conclusions: These findings underscore the importance of implementing targeted biosecurity measures and monitoring programs to mitigate the spread of mastitis-causing pathogens and enhance antimicrobial stewardship in the Irish dairy industry, while it also highlights the significance of including a One Health perspective in surveillance programs.